2005
DOI: 10.1139/w05-011
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 2 ultrafiltration systems for the concentration of seeded viruses from environmental waters

Abstract: The use of ultrafiltration as a concentration method to recover viruses from environmental waters was investigated. Two ultrafiltration systems (hollow fiber and tangential flow) in a large- (100 L) and small-scale (2 L) configuration were able to recover greater than 50% of multiple viruses (bacteriophage PP7 and T1 and poliovirus type 2) from varying water turbidities (10–157 nephelometric turbidity units (NTU)) simultaneously. Mean recoveries (n = 3) in ground and surface water by the large-scale hollow fib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 28 publications
3
34
0
Order By: Relevance
“…In two early studies of hollowfiber UF, Bicknell et al and Dziewulski and Belfort reported recovery efficiencies of 76 to Ͼ100% and 80 to 100%, respectively, for poliovirus seeded into 100-liter tap water samples (5,9). While no recent research studies have reported microbial recovery data for hollow-fiber UF techniques applied to largevolume finished water or tap water samples, the data from the present study are similar to virus recovery data (70 to 80% recovery efficiencies) reported by Olszewski et al for 100-liter groundwater samples (16).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In two early studies of hollowfiber UF, Bicknell et al and Dziewulski and Belfort reported recovery efficiencies of 76 to Ͼ100% and 80 to 100%, respectively, for poliovirus seeded into 100-liter tap water samples (5,9). While no recent research studies have reported microbial recovery data for hollow-fiber UF techniques applied to largevolume finished water or tap water samples, the data from the present study are similar to virus recovery data (70 to 80% recovery efficiencies) reported by Olszewski et al for 100-liter groundwater samples (16).…”
Section: Discussionsupporting
confidence: 88%
“…Research studies focused on developing hollow-fiber UF water sampling methods have shown that this technique can be effective for recovering diverse waterborne microbes (12,(15)(16)(17). These studies have shown that a number of procedures can be effective for minimizing attachment of microbes to UF membranes and for detachment of those microbes which do become adhered to UF membranes.…”
Section: Discussionmentioning
confidence: 99%
“…To date, no studies investigating the recovery of infectious enteric viruses by UF have utilized MNV-1 or PRD1 as a model viral surrogate for HuNoVs and HuAdVs, respectively. Moreover, few studies have reported using tangential-flow UF for the recovery and molecular detection of viral surrogates and endogenous viruses from large-volume finished drinking water samples and their source waters (29,32). Additionally, studies using molecular detection of viruses in UF concentrates have not controlled for potential false negatives by systematically evaluating sample inhibition.…”
mentioning
confidence: 99%
“…Ultrafiltration, i.e. tangential flow filtration (TFF) and hollow-fiber ultrafiltration, based on size exclusion or entrapment of viral particles to a filter matrix, has emerged as the most promising methods for virus concentration from large volumes of water (Gibson and Schwab, 2011;Hill et al, 2005;Olszewski et al, 2005;Polaczyk et al, 2008;Rhodes et al, 2011). Furthermore, these methods have been optimized for the simultaneous concentration of multiple microorganisms (e.g., enteric bacteria, protozoa, and viruses) from diverse water matrixes, including source and finished drinking water, tap water, surface water, and reclaimed water (Gibson and Schwab, 2011;Hill et al, 2007;Hill et al, 2005;Liu et al, 2012;Morales-Morales et al, 2003;Polaczyk et al, 2008).…”
Section: Detection Methodsmentioning
confidence: 99%